Penanganan Sengketa Bisnis Rental Kendaraan di Bali: Evaluasi Urgensi Legalitas Wna dan Kepatuhan Visa - I Gede Wisnu Darma Suta; Ni Ketut Sari Adnyani; Komang Febrinayanti Dantes (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study examines the urgency of foreign nationals' (WNA) legal status and visa compliance in the vehicle rental business in Bali, as well as its impact on business disputes involving local entrepreneurs. The increasing number of international tourists visiting Bali has spurred the growth of vehicle rental services, yet it has also given rise to illegal practices by foreign nationals such as misuse of tourist visas for commercial purposes, tax evasion, and unfair business competition. This research adopts a normative juridical method using statute, conceptual, and case approaches, referring to key legal documents including Law No. 6 of 2011 on Immigration, Law No. 6 of 2023 on Manpower, Ministerial Regulation No. 21 of 2016, and Bali Regional Regulation No. 5 of 2016 on Tour Guiding. The findings highlight the vulnerability of rental contracts under Article 1548 of the Indonesian Civil Code, risks of breach of contract, and widespread violations of the Electronic Traffic Law Enforcement (ETLE) system, the penalties of which are imposed on rental owners. Nationality disparities and weak immigration oversight further undermine the effectiveness of law enforcement. This study concludes that legal protection for local business actors relies heavily on the legal clarity of WNA status, the appropriateness of 1 visa categories, and strong inter-agency coordination. The novelty of this research lies in integrating legal analysis of WNA legitimacy with a dispute resolution framework specific to the vehicle rental sector in Bali’s tourism landscape a perspective that has been largely overlooked in prior studies. The recommendations include strengthening rental contracts, enhancing coordinated supervisory mechanisms, and harmonizing civil and criminal law to establish a stronger deterrent effect.